Microablative Fractional Radiofrequency as a Therapeutical Option for Genitourinary Syndrome of Menopause: Perspectives - Kamilos, Márcia Farina; Costa, Ana Paula Ferreira; Sarmento, Ayane Cristine Alves; Eleutério, José; Gonçalves, Ana Katherine (Frontiers in Reproductive Health, 2021)
The genitourinary syndrome in menopause can occur at different stages of life, with different causes or triggering factors, such as prolonged use of antiestrogens, chemotherapy, radiotherapy, and extensive vaginal surgeries, which can alter vascularization, hydration, collagen quality, and tissue elasticity. Despite hormonal therapy being considered the best evidenced treatment for genitourinary syndrome of menopause (GSM), there are limitations concerning the latter. Thus, alternative, complementary, or even substitutive treatments have emerged, such as energy use, promoting thermal tissue stimulation to improve tropism. Due to its practicality and feasibility, the micro ablative fractional radiofrequency (MAFRF) has gained space among these energies. It uses high-frequency electromagnetic waves and promotes thermal micro points in the superficial and deep dermis. The safety of these energies limits thermal action laterality and depth. Laterally, it is essential for an adequate regenerative effect without scarring marks or sequelae; the appropriate depth is important for stimulating the obligatory tissue repair response with the production and reorganization of collagen, elastic fibers, increased vascularization and hydration, and the consequent improvement in tropism. In gynecology, the MAFRF is used with therapeutic indication and functional improvement; it is applied to the entire length of the vaginal walls, the vulvar vestibule, urethral meatus, labia minora, clitoris prepuce, labia majora, perineum, and perianal region. The MAFRF has been proved to be an effective and safe treatment for GSM, with long-lasting effects, significantly reducing symptoms and improving vaginal tropism. This review aims to analyze the MAFRF as a non-hormonal therapeutic option for GSM.